Length-weight relationship of six loach species from tropical forest streams in Sarawak, Malaysia - Chen, Lin Soo; Lee, Nyanti; Nur Ezaimah, Idris; Teck, Yee Ling; Siong, Fong Sim; Jongkar, Grinang; Suan, Karen Ping Lee; Tonny, Ganyai (John Wiley & Sons Ltd., 2021)
Length weight relationships (LWRs) are presented for six loach species belonging to two families of Gastromyzontidae and Nemacheilidae captured in the Baleh River Basin, Sarawak, Malaysia. One time sampling was conducted at each station representing first- to fourth-order tributaries in the Baleh River Basin from April 2014 to November 2015. Loach samples were collected via electrofishing method and measured for total length to the nearest 0.1 cm and weighted to the nearest 0.1 g immediately after capture. The values of the equation parameter ‘b’ of the LWR falls within the range of 2.5 to 3.5 for six loach species in Sarawak, Malaysia.